Bibliometric Analysis: The Influence of Organizational Culture on Generation Z's Job Satisfaction Lifestyle - Ahmad Riyadh Umar Balahmar; Totok Wahyu Abadi (Academia Open, 2025)
In the era of globalization and rapid technological development, organizations are faced with the demands of rapid adaptation to maintain competitiveness, with organizational culture and employee commitment as key success factors. In Indonesia, Generation Z, which now dominates the workforce, has unique characteristics and high challenges in job satisfaction, which impact turnover intentions and organizational turnover. This study aims to examine the relationship between organizational culture, organizational commitment, and job satisfaction of Generation Z employees using a bibliometric analysis approach on related publications (2011-2023) collected through Publish or Perish software and analyzed with VOSViewer. The results show a significant upward trend in publications, a strong link between the topics of Generation Z, job satisfaction, and employee performance, and the important role of an adaptive and inclusive organizational culture in increasing the motivation and loyalty of Generation Z. This study provides a strong foundation for human resource management practices that are responsive to demographic dynamics and the challenges of the modern workplace. Highlights: Adaptive Culture: Inclusive organizational culture improves motivation and loyalty of Gen Z employees. Job Satisfaction: Directly linked to turnover intentions and overall organizational performance. Research Insight: Bibliometric analysis (2011–2023) shows strong publication growth in Gen Z and HR topics. Keywords: organizational culture, job satisfaction, Generation Z, organizational commitment, bibliometric analysis